m6A‐Modified SNRPA Controls Alternative Splicing of ERCC1 Exon 8 to Induce Cisplatin Resistance in Lung Adenocarcinoma - Weina Fan; Jian Huang; Fanglin Tian; Xin Hong; Kexin Zhu; Yuning Zhan; Xin Li; Xiangyu Wang; Xin Wang; Li Cai; Ying Xing (Advanced Science)
Abstract Alternative splicing (AS) generates protein diversity and is exploited by cancer cells to drive tumor progression and resistance to many cancer therapies, including chemotherapy. SNRPA is first identified as a spliceosome‐related gene that potentially modulates resistance to platinum chemotherapy. Both the knockout or the knockdown of SNRPA via CRISPR/Cas9 and shRNA techniques can reverse the resistance of cisplatin‐resistant lung adenocarcinoma (LUAD) cells to cisplatin. SNRPA overexpression enhanced the resistance of cisplatin‐sensitive LUAD cells. Gene Ontology (GO) analysis reveals that SNRPA is associated with DNA damage repair. Depletion of SNRPA induced ERCC1 exon 8 skipping and reduced ERCC1–XPF complex formation, whereas SNRPA overexpression exerted the opposite effect. siRNAs targeting isoforms containing ERCC1 exon 8 [ERCC1‐E8 (+)] reversed SNRPA‐enhanced cisplatin resistance and DNA damage repair. Furthermore, the IGF2BP protein, an m6A reader, and the ELAVL1 protein, an RNA stabilizer recruited by IGF2BP1, are found to bind to the SNRPA mRNA. ELAVL1 promoted cisplatin resistance, DNA repair and ERCC1‐E8 (+) expression in an SNRPA‐dependent manner. In a mouse xenograft model, SNRPA‐KO CRISPR enhanced the sensitivity of LUAD cells to cisplatin. Overall, this study illuminates the role of SNRPA in platinum‐based drug resistance, thereby providing a novel avenue to potentially enhance chemosensitivity and improve the prognosis of patients with LUAD.